Benthic myodocopid Ostracoda (Philomedidae) from the Southern Ocean - Chavtur, Vladimir G.; Keyser, Dietmar (Zootaxa, 2016)
This study is based on the material of myodocopid ostracodes of the family Philomedidae collected by the Russian Antarctic Polar Expeditions (1963–2007) and the Germany Expeditions on R/V “Polarstern” (1990–2002) from the continental shelf and upper slope near the Mawson and Davis stations, the Weddell Seas, the region of the South Shetland Islands near the Russian Polar station “Molodezhnaya” and adjacent waters. Eight philomedid species belonging to two genera were identified in these collections. Scleroconcha tuberculata sp. nov. is described and figured as a new species. Additional descriptions and figures for the species S. gallardoi Kornicker, 1971, Philomedes assimilis Brady, 1907, P. charcoti Daday, 1908, P. heptatrix Kornicker, 1975, P. rotunda Skogsberg, 1920, P. orbicularis Brady, 1907 and P. tetrathrix Kornicker, 1975 are given. Keys for all species of the mentioned genera known from the Southern Ocean are presented. A list of sampling stations and species collected is provided in the Appendix 1.